THE INFLUENCE OF DUTCH COLONIALISM ON THE DEVELOPMENT OF THE ISLAMIC MATARAM KINGDOM IN JAVA, 1749–1755 - Siti Fadira Masbait; Triwahana (CV. Fahr Publishing, 2025)
This study aims to: (1) Understand the process of the entry of Dutch colonialism into the Islamic Mataram Kingdom (2) the influence of Dutch colonialism on the Islamic Mataram Kingdom between 1749 and 1755 (3) the impact of Dutch colonialism on the development of the Islamic Mataram Kingdom. The method used in this study is a literature review, which is carried out through identifying sources that have been obtained such as history books, scientific journals, archives and the study of other primary sources. This study also uses steps that include heuristics, source criticism, interpretation and historiography. The results of this study have the following conclusions: (1) Dutch colonialism entered Mataram through the involvement of the VOC in internal palace conflicts, especially between Prince Mangkubumi and Pakubuwana III (2) The influence of colonialism is seen from the dominance of the VOC in political decision-making, the formation of alliances, and control over local rulers. This culminated in the Giyanti Agreement in 1755 which divided Mataram into two weak powers that were easy to control. (3) The impact was very large on the politics, social, and culture of Mataram. The government system Traditional government was replaced by colonial bureaucracy, the king's power was limited, and the kingdom's culture and independence were displaced by Dutch colonial interests.